The role of exosomes in the pathogenesis and management of diabetic kidney disease: a systematic review and meta-analysis - Zheng, Yan; Xu, Chu; Jin, Yan (Frontiers in Endocrinology, 2024)
for studies that compared the levels of exosomes between patients with diabetic kidney disease and controls published up to November 27, 2023. Methodological quality was assessed using the JBI Appraisal Checklist for Case-Control Studies. The methodology of the samples and main results were summarized. A meta-analysis of the diagnostic performance of exosomes was performed using estimates of test sensitivity and specificity, and these values were summarized using summary receiver-operating characteristic curves. The reporting of thisresults were reported review followeding the PRISMA 2020 checklist. Results: A total of 32 Thirty-two studies, with including 1119 patients with diabetic kidney disease and 1328 controls, met the inclusion criteria. This review identifiedA total of 78 upregulated and 22 downregulated microRNA, two 2 upregulated and four 4 downregulated mRNA, six 6 upregulated and one 1 downregulated protein, and four 4 upregulated lipids were identified. The dysregulation of miR-126, miR-145, miR-150, miR-21, and WT1 mRNA dysregulation was were consistently reported in at least two studies. We found thatThe exosomes' overall sensitivity and specificity of exosomes in diabetic kidney disease diagnosis were 0.70 (95% CI: 0.59-0.80) and 0.79 (95% CI: 0.70-0.85), respectively. The summary receiver operator characteristic curve was plotted to assess diagnostic accuracy with the area under the curve (AUC) of 0.82 (95% CI: 0.78-0.85).Exosomes have great potential to become effective diagnostic biomarkers for diabetic kidney disease. Panels of exosomes or the combination of exosomes with other clinical indicators seemed more accurate than single exosomes.